FRI0447 Temporomandibular Joint and Chewing Features in Systemic Sclerosis Patients: A Clinical and Magnetic Resonance Imaging Analysis. (9th June 2015) - Matarese, G.; Isola, G.; Alibrandi, A.; Lo Gullo, A.; Bagnato, G.; Cordasco, G.; Perillo, L.
Abstract : Background: The pathogenesis of Systemic Sclerosis (SSc) remains unknown, but increasing evidence suggests that activation of lesional fibroblasts contributes to the fibrotic process. SSc is characterized by symmetric, erosive synovitis, which may result in joint irregularity and disability. Objectives: The purpose of this clinical study was to assess the prevalence and characteristics of Temporomandibular joint (TMJ) symptoms, clinical and Magnetic Resonance Imaging (MRI) findings in a cohort of patients with SSc. Methods: 27 patients with SSc (12 Diffuse, 15 Limited, mean age 53.9, SD ±1.2) and 28 healthy subjects (mean age 54.8, SD ±4.2) were enrolled in this cohort study. Oro-facial clinical examination for assessing the presence of TMJ sounds, pain in the TMJ area, tenderness of masticatory muscles, limited mouth opening, pain assessment, MRI scan and Anamnestic and Dysfunctional Index were achieved in all of patients. Results: The test groups presented more clinical and MRI TMJ symptoms and dysfunction than Control group. The distributions of symptoms were significantly different (P<0.05), in the Test groups for TMJ sounds, pain during mandibular movement and difficulty in the maximum mouth opening. There was also a significant decrease (P<0.001), in the Test groups, in the mean of leftward, rightward laterotrusion and protrusion. Correlation analysis showed that maximum opening leftward laterotrusion, protrusion and click were significantly correlated to Modified Rodnan Skin Score. The mean duration of disease was significantly correlated, ever in Total SSc group, only for the maximum mouth opening value. Conclusions: This study proves that TMJ dysfunction is a common feature in SSc patients and it is correlated with a extent and involvement of disease and supports the notion that TMJ examination should be encouraged in rheumatology and clinicians should provide a patient support and a right pain management. References: Jelaska A, Arakawa M, Broketa G, Korn JH. Heterogeneity of collagen synthesis in normal and systemic sclerosis skin fibroblasts: increased proportion of high collagen–producing cells in systemic sclerosis fibroblasts. Arthritis Rheum 1996;39:1338–46. Schieir O, Thombs BD, Hudson M, Boivin JF, Steele R, Bernatsky S, et al. Canadian Scleroderma Research Group. Prevalence, severity, and clinical correlates of pain in patients with systemic sclerosis. Arthritis Care Res (Hoboken). 2010;62:409-17. Disclosure of Interest: None declared